Utilização de água salobra e rejeito de dessalinizador na germinação e produção de mudas de moringa oleifera lamarck - Silva, Lunara Grazielly Costa da (Universidade Federal Rural do Semi-Árido, 2018)
The Moringa oleifera Lamarck is an arboreal species that has been adapted to the soil and climatic conditions of the semi-arid region of the Brazilian Northeast, because it has several uses, such as fodder, medicinal and culinary, in the cosmetics industry, the production of seedlings of this species can generate a source of income for the population. This work aims to evaluate the germination and production of Moringa oleifera seedlings with the use of brackish water and desalter reject. The research was conducted in the greenhouse of the Federal Rural Semi-Arid University, Mossoró-RN, in a completely randomized design with four hydric sources obtained in the Jurema settlement in the rural area of Mossoró. The treatments were: water after passing through the desalter (0,32 dS.m-1 - T1); water obtained from the well of the Neci Campos Municipal School, located in the settlement (6,16 dS.m-1 - T2); water obtained in the well that supplies the settlement (7,07 dS.m-1 - T3) and desalter reject water (10,35 dS.m-1 - T4). Two experiments were carried out, in which the first one evaluated the germination, and the second experiment evaluated the development of the seedlings. For the first experiment, there was no significant difference between the treatments in the germination and in relation to the root length of the seedlings. For the second experiment, the height and diameter of the collection were not affected, the leaf dry matter production was affected in the T3 and T4 treatments, when they presented a reduction of 26% and for the dry matter yield of the roots was higher for saline treatments. According to the results, it was concluded that moringa is a salinity-tolerant species for germination and development of saplings and desalter reject of up to 10,35 dS.m-1, being possible the production of seedlings for the small producer, in order to obtain an extra income and to avoid the discarding of the brackish water and the desalter waste in the soil, avoiding the contamination of the soils.
Keywords: Rejeito de dessalinizador; Semiárido; Moringa oleifera; Rejection of desalter; Semiarid; Moringa oleifera; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL